HDL in sepsis – risk factor and therapeutic approach - Morin, Emily E.; Guo, Ling; Schwendeman, Anna; Li, Xiang-An (Frontiers in Pharmacology, 2015)
High-density lipoprotein (HDL) is a key component of circulating blood and plays essential roles in regulation of vascular endothelial function and immunity. Clinical data demonstrate that HDL levels drop by 40-70% in septic patients, which is associated with a poor prognosis. Experimental studies using Apolipoprotein A-I (ApoAI) null mice as an HDL deficient model showed that mice lacking HDL are susceptible to septic death, and overexpressing ApoAI in mice to increase HDL levels protects against septic death. These clinical and animal studies support our hypothesis that a decrease in HDL level is a risk factor for sepsis, and raising circulating HDL levels may provide an efficient therapy for sepsis. In this review, we discuss the roles of HDL in sepsis and summarize the efforts of using synthetic HDL as a potential therapy for sepsis.